New evidence on technological acceptance model in preschool education: Linking project-based learning (PBL), mental health, and semi-immersive virtual reality with learning performance - Zang, Juanjuan; Kim, Youngsoon; Dong, Jihe (Frontiers in Public Health, 2022)
Despite significant research on student learning performance, the literature on preschool education is limited. The learning performance of different institutes in China has not been satisfactory, and students are not given enough technological resources to help them improve their learning performance. Although Chinese preschool students are active learners, their learning performance is inadequate. As a result, this research aimed to discover how project-based learning, semi-immersive virtual reality, and mental health influence learning performance. For data collection, 800 questionnaires were distributed to high schools, and 290 valid questionnaires were considered for the data analysis using Smart PLS-SEM. According to the study's findings, project-based learning is critical for improving learning performance. This study's findings are significant because they show that mental health and semi-immersive virtual reality significantly mediate the relationship between project-based learning and learning performance. The study's findings are critical for educational institutions interested in improving student performance through project-based learning opportunities. Furthermore, because it employs an innovative technology acceptance model, this study has significant practical implications for project-based learning and student learning performance.